Маркетингова комунікаційна політика торговельного підприємства у сфері моди (на прикладі магазину вишиванок) - Сав'юк, Надія Володимирівна; Saviuk, Nadiia Volodymyrivna (Національний університет "Львівська політехніка", 2024)
Глобальний споживчий ринок дедалі більше зацікавлений в унікальних історіях брендів, які втілюють у собі не лише естетичну привабливість, а й культурну цінність. Продукт, створений на основі народних традицій, має значно потужніший емоційний імпульс, ніж стандартні пропозиції, позбавлені глибокої історичної складової [1]. Значною мірою забезпечити основну мету компанії можливо через розробку ефективної комунікаційної політики. За умов високої конкуренції на ринку забезпечення стратегічного розвитку компанії та її довгострокового існування в індустрії моди потребує стратегічного підходу до питання формування маркетингового плану комунікацій з клієнтами з позиції практичності та перспективності [2]. Сучасні умови ведення бізнесу дозволяють формувати пропозицію у сфері моди, оскільки ринок насичений великою кількістю компаній, які здійснюють виробництво фешен товарів. Такий ринок також характеризується глобалізаційними та інноваційними процесами, які зумовлюють високі вимоги серед клієнтів, які відчувають потребу у якісних та індивідуалізованих товарах, тому компаніям потрібно шукати інструменти індивідуалізації та ексклюзивності [3]. Важливо знати при яких умовах та причи нах погляди на бренд у потенційних спожива чів можуть змінитись. Бренд досягає успіху, коли робить культурний прорив. А, брендинг є набором прийомів, призначених для створення соціальної течії [4]. Споживання за сучасних умов більшою мірою доцільно розглядати через призму рефлексій, тобто самоусвідомлення [5]. Об’єктом дослідження в бакалаврській кваліфікаційній роботі являється ФОП Олійник О.П., основним видом діяльності якого є збут вишиванок бренду 5 SVARGA. SVARGA — позиціонує себе як український бренд вишитого одягу, що прокладає місток між українськими старовинними орнаментами і сучасністю. Базою чи основою для колекцій SVARGA є найстаровинніші, автентичні взірці вишиваного одягу. Політика компанії у питання якості надзвичайно важлива та строга, вишитий одяг шиється з натуральної тканини, а моделі та ескізи постійно вдосконалюємося. Бренд SVARGA з любов’ю береже й поширює код нації, щоб кожен з українців пам’ятав про своє походження. Компанія має власні виробничі потужності розташовані у м Львів, а також на сьогодні в мережі є 5 брендованих магазинів, серед числа яких магазин вишиванок ФОП Олійник О.П. Предметом дослідження в бакалаврській кваліфікаційній роботі маркетингова діяльність ФОП Олійник О.П. Метою бакалаврської кваліфікаційної роботи є дослідження комунікаційної політики торгівельного підприємства сфери моди, зокрема в контексті формування пропозицій щодо її покращення. Результати дослідження полягають у розробці рекомендацій щодо покращення комунікаційної політики, через дослідження ефективності сайту компанії за визначеними показниками, а також порівняння з сайтами конкурентів. Визначення інтегральної оцінки сайту дозволить запропонувати рекомендації щодо зміни структури сайту задля підвищення його ефективності та сприйняття клієнтами.

The global consumer market is increasingly interested in unique brand stories that embody not only aesthetic appeal, but also cultural value. A product created on the basis of folk traditions has a much stronger emotional impulse than standard offers devoid of a deep historical component [1]. To a large extent, it is possible to ensure the main goal of the company through the development of an effective communication policy. In conditions of high competition in the market, ensuring the strategic development of the company and its long-term existence in the fashion industry requires a strategic approach to the issue of forming a marketing plan for communications with customers from the standpoint of practicality and prospects [2]. Modern business conditions allow you to form an offer in the fashion sector, since the market is saturated with a large number of companies that produce fashion goods. Such a market is also characterized by globalization and innovation processes, which lead to high demands among customers who feel the need for high-quality and individualized goods, so companies need to look for tools for individualization and exclusivity [3]. It is important to know under what conditions and reasons the views of potential consumers on the brand can change. A brand achieves success when it makes a cultural breakthrough. And, branding is a set of techniques designed to create a social trend [4]. Consumption in modern conditions is more appropriate to consider through the prism of reflections, that is, self-awareness [5]. The object of research in the bachelor's qualification work is the sole proprietor Oliynyk O.P., whose main activity is the sale of embroidered clothes of the SVARGA brand. SVARGA positions itself as a Ukrainian brand of embroidered clothing that bridges the gap between Ukrainian ancient ornaments and modernity. 8 The base or foundation for SVARGA collections are the oldest, authentic samples of embroidered clothing. The company's quality policy is extremely important and strict, embroidered clothing is sewn from natural fabric, and models and sketches are constantly being improved. The SVARGA brand lovingly preserves and spreads the code of the nation so that each Ukrainian remembers their origin. The company has its own production facilities located in Lviv, and today there are 5 branded stores in the network, including the embroidery shop of Oliynyk O.P. The subject of research in the bachelor's qualification work is the marketing activities of Oliynyk O.P. The purpose of the bachelor's qualification work is to study the communication policy of a trading enterprise in the fashion sector, in particular in the context of forming proposals for its improvement. The results of the study are to develop recommendations for improving the communication policy, through research on the effectiveness of the company's website according to certain indicators, as well as comparison with competitor websites. Determining the integral assessment of the site will allow us to offer recommendations for changing the structure of the site in order to increase its effectiveness and perception by customers.
Marketing communication policy of a trading enterprise in the field of fashion (on the example of an embroidery shop)
Keywords: 6.075.00.00; маркетингова комунікаційна політика; торгівельне підприємство; бренд; сфера моди; клієнти; інструменти маркетингу; marketing communication policy; trading company; brand; fashion industry; clients; marketing tools. List of used literature sources. 1. Perevozova I.V.; Parkhomchuk S. S. The influence of cultural heritage on the brand of embroidery: from traditions to modern marketing strategies / Economy and Society. Issue No. 72 / 2025. DOI: https://doi.org/10.32782/2524-0072/2025-72-93 2. Ustilovska A.S.; Bozhiday I.I. The main theoretical principles of the enterprise's communication policy. Current issues in modern science. No. 2 (22); 2022. P. 138-150. 9 3. Bondarenko S.M.; Palagin Yu.O.; Bondarenko B.S. Improving the assortment policy of a trading enterprise in the field of fashion / Economy and Society. Issue No. 16 / 2018. URL: https://economyandsociety.in.ua/journals/16_ukr/40.pdf 4. Lykholat S.; Zadorizhna I. M. The influence of the brand on consumer behavior in the context of covid-19. Economy and Society. 2021. Issue 26. URL: https://economyandsociety.in.ua/index.php/journal/article/view/331 5. Bil M. M. Consumer behavior of the population of Ukraine: reflections on the COVID-19 pandemic. In the book. Socio-economic problems of the modern period of Ukraine: Issue 149 (3). 2021. DOI: https://doi.org/10.36818/2071-4653-2021-3-2